Influence of Nutrition and Maternal Bonding on Postnatal Lung Development in the Newborn Pig - Schlosser-Brandenburg, Josephine; Ebner, Friederike; Klopfleisch, Robert; Kühl, Anja A.; Zentek, Jürgen; Pieper, Robert; Hartmann, Susanne (Frontiers in Immunology, 2021)
Background: Microbial colonization and immune cell maturation coincide at mucosal sites and are decisive for postnatal lung development. How external factors influence neonatal pulmonary immune development is poorly understood. Objective: To elucidate the impact of key determinants in early life, nutrition and maternal bonding, on postnatal lung maturation in a human-relevant animal model. To investigate the underlying immunological changes of impaired lung maturation and study the mechanisms of conversion. Methods: Newborn piglets were kept with or without isolation from their mothers and fed bovine milk-based infant formula or received sow's milk. Lung growth, histomorphology, respiratory immune responses, and lung microbiota were analyzed. Mother- and sow-milk-deprived piglets received maternal material or were reintroduced to the maternal environment at varying intervals to study options for reversal. Results: Formula feeding combined with isolation of newborn piglets resulted in disturbed postnatal lung maturation. Reduced lung growth correlated with dampened IL-33 expression, impaired lung myeloid cell activation, and decreased Th1 differentiation, along with diminished richness and diversity of the lung microbiota. Transfer of bacteria-enriched maternal material reversed the negative effects on pulmonary immune maturation. Early (within 3 days) but not late (within 7 days) reintroduction to the mother allowed restoration of normal lung development. Conclusion: Our findings reveal that lung growth, respiratory immunity, and microbial lung colonization in newborns depend on postnatal diet and maternal contact, and targeting these key regulators could promote lung development during this critical life stage.